Polemik Agamawan dan Saintis Seputar Covid-19: Menilik Gagasan Integrasi Agama dan Sains Perspektif Mehdi Golshani - Bistara, Raha (IAIN Surakarta, 2020)
This article examines Mehdi Golshani thoughts on the integration of knowledge, which is integration between sacred sciences and secular sciences during the Covid-19 pandemic. The debates that have arisen in the community between religious people and scientists regarding Covid-19 can be resolved if they are put together in a science forum. For this reason, Mehdi Golshani came up with a new idea that was different from the previous Muslim scientific ideas. Mehdi Golshani's solution regarding the debate between religion and science is not deconstruction, reconstruction, or reconciliation. However, to find answers of questions in society about the contributions of religionists and scientists is a method of integration with the Islamic science formula. The conclusion of this article is that science and Islam are an integral part that cannot be separated or even disputed. Science desperately needs divine and religious entities to be filled with a scientific dimension. Â